Cefoperazone concentrations in bile and gall bladder wall after intravenous administration. - Nakamura, T (1980)
Cefoperazone concentrations in the common duct bile, gall bladder bile, and gall bladder wall were determined in four patients with cholelithiasis and one patient with carcinoma of the head of the pancreas, all of whom had normal renal functions. Within 65 min after a 1-g intravenous administration, maximum concentrations ranged from 373.4 to 3,100 micrograms/ml in common duct bile and from 6.8 to 680 micrograms/ml in gall bladder bile. Cefoperazone concentrations per gram of the gall bladder wall ranged from 16.8 to 48.0 micrograms.